2017
DOI: 10.14740/jem364w
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active Antiretroviral Therapy-Associated Metabolic Syndrome and Lipodystrophy: Pathophysiology and Current Therapeutic Interventions

Abstract: The use of highly active antiretroviral therapy (HAART) has extremely enhanced the clinical outcome of HIV disease with a decrease in mortality and morbidity. However, the inclusion of protease inhibitors (PIs) and nucleoside reverse transcriptase inhibitors (tNRTIs) has strongly been linked to the development of metabolic abnormalities and lipodystrophy. Lipodystrophy is defined by the loss of peripheral subcutaneous fat and central adiposity, mainly in the abdomen, breast and dorsocervical region. These diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 147 publications
0
5
0
Order By: Relevance
“…Although the pathogenesis of HALS is not yet fully understood, it is known to be multifactorial and probably the result of the interaction between ART, viral infection, genetic factors, and the individual's lifestyle (12,13). The association between lipodystrophy and ART is the most studied and well-established in the literature, especially regarding to protease inhibitors and reverse transcriptase inhibitors (14)(15)(16)(17), but some studies described positive cases in which there was no treatment and even so presented changes in body fat composition (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Although the pathogenesis of HALS is not yet fully understood, it is known to be multifactorial and probably the result of the interaction between ART, viral infection, genetic factors, and the individual's lifestyle (12,13). The association between lipodystrophy and ART is the most studied and well-established in the literature, especially regarding to protease inhibitors and reverse transcriptase inhibitors (14)(15)(16)(17), but some studies described positive cases in which there was no treatment and even so presented changes in body fat composition (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…The audience insights also suggested that the fear is associated with the desire to belong and concerns over loss of control that can result from being discriminated against by community members upon testing positive. These concerns are supported by studies that have described the lack of control PLHIV, including men, experience over physical changes, such as lipodystrophy, that serve as clinical manifestations of HIV and make the disease visible as a potential source for stigma and social withdrawal ( Alexias et al, 2016 ; Carr, 2014 ; Gagnon & Holmes, 2012 ; Njelekela et al, 2017 ; Nyamaruze & Govender, 2020 ; Nzuza et al, 2017 ). Other studies have also reported on the stigma, discrimination, and isolation that PLHIV experience ( Gilbert & Walker, 2010 ; Maman et al, 2002 , 2009 ; Mbonu et al, 2009 ; Mlay et al, 2008 ; Roura et al, 2009 ; Wingood et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“… Cohort USA Safar Zadeh E et al, 2013 28 Leptin replacement therapy ameliorated both the metabolic and hepatic abnormalities of lipodystrophy. Improvements in non-alcoholic steatohepatitis (NASH) score presumably represents stabilization or improvement of the course of the disease Review Nzuza S et al, 2017 29 If lipodystrophy is not carefully managed, it may ultimately predispose a significant number of patients to increased risks of metabolic syndrome, diabetes and cardiovascular diseases. Cross-sectional Israel Tsiodras S et al, 2019 30 Adherence to a Mediterranean dietary pattern was favorably related to cardiovascular risk factors in HIV-positive patients with fat redistribution.…”
Section: Forms Of Lipodystrophy Syndromesmentioning
confidence: 99%
“… Cross-sectional Israel Tsiodras S et al, 2019 30 Adherence to a Mediterranean dietary pattern was favorably related to cardiovascular risk factors in HIV-positive patients with fat redistribution. Challenges related to lipodystrophy Review Nzuza S et al, 2017 29 Lipodystrophy related cosmetically distressing and socially stigmatizing for many patients leading to decreased adherence to antiretroviral therapy. Cross-sectional and comparative Brazil Siqueira LR et al, 2021 7 Lipodystrophy negatively affects the self-esteem of HIV infected people and this made it difficult to adhere to ART.…”
Section: Forms Of Lipodystrophy Syndromesmentioning
confidence: 99%